Association of 25-hydroxyvitamin D with areal and volumetric measures of bone mineral density and parathyroid hormone: impact of vitamin D-binding protein and its assays. Issue 2 (February 2016) - Jemielita, T.; Leonard, M.; Baker, J.; Sayed, S.; Zemel, B.; Shults, J.; Herskovitz, R.; Denburg, M.
Abstract Summary A comparison of the association of different forms of 25-hydroxyvitamin D [25(OH)D] with parathyroid hormone (PTH) and with areal and volumetric bone mineral density (BMD) demonstrated that bioavailable and free 25(OH)D do not provide a better index of vitamin D status in terms of bone health compared to total 25(OH)D. Introduction This study aims to compare measures of vitamin D-binding protein (DBP) using a monoclonal versus polyclonal ELISA and assess correlations of total versus estimated free and bioavailable 25(OH)D with BMD and PTH concentrations. Methods DXA and peripheral quantitative CT (pQCT) scans were obtained in 304 adults (158 black, 146 white), ages 21–80 years. Free and bioavailable 25(OH)D were calculated from total 25(OH)D, DBP, and albumin concentrations. Multivariable linear regression with standardized beta coefficients was used to evaluate associations of bone measures and PTH with total, free, and bioavailable 25(OH)D. Results Measures of DBP obtained using a monoclonal versus polyclonal ELISA were not correlated (r s  = 0.02, p  = 0.76). Free and bioavailable 25(OH)D based on the polyclonal assay were lower in black versus white participants (p  < 0.0001); this race difference was not evident using the monoclonal assay. Adjusted for age, sex, calcium intake, and race, all forms of 25(OH)D were negatively associated with PTH, but the absolute coefficient was greatest for total 25(OH)D (−0.34, p  < 0.001) versus free/bioavailable 25(OH)D (−0.18/−0.24 depending on DBP assay, p  ≤ 0.003). In analyses stratified on race, none of the measures of 25(OH)D were associated with BMD across DXA and pQCT sites. Conclusions The monoclonal versus polyclonal ELISA yielded highly discrepant measures of DBP, particularly among black individuals, likely related to established race differences in DBP polymorphisms. Contrary to prior studies, our findings indicate that using DBP to estimate bioavailable and free 25(OH)D does not provide a better index of vitamin D status in terms of bone health.